Chiral gold(I) vs chiral silver complexes as catalysts for the enantioselective synthesis of the second generation GSK-hepatitis C virus inhibitor - Martín-Rodríguez, María; Nájera, Carmen; Sansano, José M.; de Cózar, Abel; Cossío, Fernando P. (Beilstein Journal of Organic Chemistry, 2011)
The synthesis of a GSK 2nd generation inhibitor of the hepatitis C virus, by enantioselective 1,3-dipolar cycloaddition between a leucine derived iminoester and tert-butyl acrylate, was studied. The comparison between silver(I) and gold(I) catalysts in this reaction was established by working with chiral phosphoramidites or with chiral BINAP. The best reaction conditions were used for the total synthesis of the hepatitis C virus inhibitor by a four step procedure affording this product in 99% ee and in 63% overall yield. The origin of the enantioselectivity of the chiral gold(I) catalyst was justified according to DFT calculations, the stabilizing coulombic interaction between the nitrogen atom of the thiazole moiety and one of the gold atoms being crucial.
Keywords: BINAP; 1,3-dipolar cycloaddition; gold; HCV; phosphoramidite; silver; viral inhibitor